Empirical validation of trust building training programme - Sharma, Chandra Shekhar (1991)
Chandra Shekhar Sharma focus on `trust building training programme' among private sector personnel with the hope of generating useful insights relevant to government and the public sector. His objective is to verify empirically the capability of the five strategies evolved for trust building and also to examine which strategy would be more suitable for superiors and which one for the subordinates. Sharma has formulated eight hypotheses covering five aspects that are supposed to build trust of trannes. The data for the study was collected on a five-point scale from 83 supereior and 32 subordinates working in private sector which was used for two experiments using various tools of statistical analysis. Thou
Keywords: Management; Organisational Behaviour; Training